If it's not what You are looking for type in the equation solver your own equation and let us solve it.
750=x*0.6+x/3+x*3
We move all terms to the left:
750-(x*0.6+x/3+x*3)=0
Domain of the equation: 3+x*3)!=0We add all the numbers together, and all the variables
We move all terms containing x to the left, all other terms to the right
x*3)!=-3
x!=-3/1
x!=-3
x∈R
-(+x*0.6+x/3+x*3)+750=0
We get rid of parentheses
-x*0.6-x/3-x*3+750=0
We multiply all the terms by the denominator
-(x*0.6)*3-x-(x*3)*3+750*3=0
We add all the numbers together, and all the variables
-(+x*0.6)*3-x-(+x*3)*3+750*3=0
We add all the numbers together, and all the variables
-1x-(+x*0.6)*3-(+x*3)*3+2250=0
We multiply parentheses
-1x-1.8x-9x+2250=0
We add all the numbers together, and all the variables
-11.8x+2250=0
We move all terms containing x to the left, all other terms to the right
-11.8x=-2250
x=-2250/-11.8
x=190+8/11.8
| 0.08+0.24(2m-3)=+0.6(8+m) | | (3x-5)(x+3)=60 | | (35x)-(x²+5x+125)=-x²+30x-125 | | 65+2x-10=180 | | 35x-x²+5x+125=-x²+30x-125 | | -12y+100=13y | | x^2=-x^2+4 | | 10x-2x=8x-3x | | 25x+110=540 | | 5(x+1)+2(5-x)=3(x+5) | | 5x+10=6x-41= | | 0.95^n=0.15 | | 51=3(27+2z) | | 3x+40=4x-6 | | 9x+10=7x+32 | | 5-x=3x | | 12b-3+6=10+20b | | 8×x/2-5/1=7x+2 | | 3×x-5=-2×4-x | | 7(x=5)=42 | | 9b–4b+3b=16 | | 4=8g-2 | | 4×1=-x+3 | | 1=p-9 | | x+10=3(x-4) | | 13x+14=3x+224 | | 4a+1/3=6a-5/7 | | 6(x-3)-2x=4(x-8) | | 7(x+3)=4x-10 | | 1=12x=-10=x | | 140=x(x+40/100) | | 7-9x=22+4x |